Kinematic analysis of drag anchor installation trajectory considering both shallow and deep anchor behavior of horizontal fluke. (July 2020) - Wu, Xiaoni; Chow, Yean Khow; Leung, Chun Fai
Highlights: A kinematic analysis of drag anchor trajectory considering both the shallow anchor behavior and deep anchor behavior is conducted; An approach of considering shallow anchor behavior is proposed and the effect of the control range of shallow yield envelopes is investigated; The effects of the shallow anchor behavior, soil shear strength profile, and interface friction condition on the trajectory prediction are investigated. Abstract: Drag anchor has been widely used for offshore mooring system. Prediction of the invisible anchor trajectory during the drag-in installation is still challenging but important for determination of anchor capacity in anchor design and guiding the field installation. Kinematic analysis based on yield envelope method provided an alternative method for anchor trajectory prediction. However, the existing analysis process is based on the assumption that the anchor fluke behaves as a deeply embedded fluke with deep localized failure during the whole installation while the practical shallow behavior is ignored. The current study aims to investigate the effect of shallow anchor behavior of a horizontal fluke on the predicted trajectory of drag anchor. It is found that the approximation of anchor shallow behavior using shallow yield envelopes from horizontal fluke introduces very slight impact on the anchor installation behavior for assumption of smooth interface regardless of the soil profile. While the degree of impact from shallow behavior for cases with rough interface is dependent on the used capacity factor for chain and shank force calculation. The influence of the soil profile is not consistent for analyses based on rough interface using different values of capacity factor. For a given drag length in the affected range, the prediction using only the deep yield envelope does predict deeper embedment depth.